Regulation of miR‐17‐92a cluster processing by the microRNA binding protein SND1. Issue 15 (13th June 2013) - Heinrich, Eva-Marie; Wagner, Jasmin; Krüger, Marcus; John, David; Uchida, Shizuka; Weigand, Julia E.; Suess, Beatrix; Dimmeler, Stefanie
Abstract : MicroRNAs are small non‐coding RNAs that regulate gene expression. Although all seven members of the miR‐17‐92a cluster originate from one primary transcript they are differentially expressed suggesting the presence of posttranscriptional regulation. By RNA pulldown and mass spectrometry we identified SND1, a known regulator of edited RNAs, interacting with pre‐miR‐92a and all mature miR‐17‐92a members. Hypoxic conditions lead to an elevation of the pri‐miR‐17‐92a transcript and significantly increased levels of the precursors whereas the mature miRs were not significantly changed. SND1 silencing resolved this block in processing and induced an increase in mature miRs. Together, SND1 might be the missing link between hypoxia and the differential regulation of miRNA processing. Abstract : Pre‐miR‐92a binding proteins were identified via RNA pulldown and mass spectrometry. The interaction of SND1 with pri‐, pre‐ and mature miR‐92a was confirmed via RNA immunoprecipitation (RIP). Hypoxic conditions induced a block in pre‐miR‐17, ‐20, ‐92 processing. Silencing of SND1 under hypoxia mimicking conditions resolved this processing block.